Quality of the wooden material in outdoor furniture - Nikoljski Panevski Elena; Kanevce, Ivo (Ss. Cyril and Methodius University in Skopje, Faculty of Design and Technologies of Furniture and Interior in Skopje, 2019)
The aim of this paper is to analyze the quality of the wooden material in outdoor furniture. For the purpose of this work is designed exterior furniture and urban equipment or set for garden. By analyzing this type of furniture and it’s needs from anthropometrical point of view there comes the need for design of several different pieces of furniture, including: chair, armchair, stool, two person bench, 3 person bench, rectangular table, square table, swing and matching flower pots. On the other side by analyzing outdoor furniture and its needs from material aspect there are certain reasons why there is use of thermo wood, and what are the positive consequences of its use. The ultimate goal is to get a quality seating and leaving outdoor in which the human factor is very important. Through better understanding of the parameters of ergonomics, the designer can improve health and safety in furniture. Actually obligation and task of the planner is to constantly monitor research in the field of ergonomics to implement, maintain and improve the design of furniture’s. Thereby are observed anthropometric standards for this type of furniture as well as the chosen material which satisfy the conditions of permanent use and desired look.
Keywords: ergonomics; anthropometry; human factor; design; construction; material; thermo wood; environment; interaction